Leveraging Memory Strategies to Enhance Vocabulary Proficiency In English Language Education At An English Course In Indonesia - Imam nur Aziz (JEET, Journal of English Education and Technology, 2024)
This study investigates the effectiveness of incorporating memory strategies to enhance students' vocabulary acquisition in an English course. The study followed a pre-experimental design and applied quantitative methods, which included three stages: pre-test assessment, memory strategy application, and post-test evaluation. The researcher used paired sample t-test analysis to assess the influence of memory methods on vocabulary acquisition, with a specific emphasis on the speaking phase. The research findings indicated a substantial enhancement in vocabulary learning, as shown by a considerable rise in the average score from 60.55 to 68.88. The reduction in standard deviation and standard error of mean further underscored the enhanced consistency and precision of the observed improvements. This research advises the ongoing incorporation of memory methods into language teaching. It offers educators and researchers invaluable information for developing dynamic and successful language learning settings. Therefore, it is essential to consider the constraints of this research. In addition, the findings of this research may serve as a foundation for the future development of more effective approaches to English language acquisition. The subsequent study is anticipated to examine the use of memory methods in a broader context of language acquisition.